Implementasi Core Values Asn Berakhlak Dalam Meningkatkan Kinerja Pegawai Di Kabupaten Garut - Zakaria, Ricky Muhamad; Hermansyah, Heri; Ramadhani, Cecep; Julianty, Liska (Mutiara: Multidiciplinary Scientifict Journal, 2025)
This research aims to find out and analyse how the implementation of the basic values of ASN BerAKHLAK in improving employee performance in Garut Regency, and to find out and analyse what are the inhibiting factors in the process of implementing the basic values of ASN BerAKHLAK in improving employee performance in Garut Regency. The research method was conducted with a descriptive qualitative approach to explore and analyse the implementation of the basic values of ASN BerAKHLAK in improving employee performance in Garut Regency. This research focuses on data collection through in-depth interviews with employees who are directly involved in public services in Garut Regency. The results revealed that the implementation of ASN BerAKHLAK basic values in Garut Regency, which consist of service-oriented, accountable, competent, harmonious, loyal, adaptive, and collaborative, is an important foundation in building an effective work culture in government agencies. These values not only improve employee performance, but also strengthen ASN's commitment to public services in Garut Regency.